Pests, diseases and disorders of peas and beans : - Biddle, Anthony J. (Manson Pub., 2007)
This book provides the most important pathogens, concise descriptions of the symptoms and cycles of diseases, their distribution and economic importance and advice on their control. The text is illustrated with some 300 color photographs of affected crops to aid in the rapid identification of disease. The book also includes 'pest profiles' that identify, with the use of color photographs, the pests that commonly prey on pea and bean crops.